RECONSTRUCTION OF EXECUTIVE AND LEGISLATIVE AUTHORITY IN MAKING GOOD GOVERNANCE (GOOD GOVERNANCE) VALUES BASED ON WELFARE - Mohamad Khamim; Wahyono Wahyono (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The purpose of this study is to analyze the forms of executive and legislative authority in ensuring good governance in the perspective of Law No. 23 of 2014 on Regional Government, to find weaknesses authority of the executive and the legislature in ensuring good governance (good governance) at this time, and to analyze the reconstruction authority of the executive and the legislature in ensuring good governance (good governance) with a valuebased welfare. Results of research conducted by the reconstruction of the executive and legislative authority in the good governance values-based welfare by making efficiency and effectiveness of executive and legislative authority that can improve public services and welfare. The reconstruction of the law by making changes to Article 63 paragraph (1), Article 65 paragraph (1) letter (f), Article 66 paragraph (3) and addition of paragraph (4), Article 88 of Law No. 23, 2014. In order to avoid head area tends to ignore the public, taking care of their own interests than the public interest / people and local elections by the people was the most correct and Parliament are tasked to supervise the government as Parliament also elected. So that Article 101 paragraph (1) letter d and the addition of d1, and Article 154 paragraph (1) letter d and the addition of the letter d1 Law 23 of 2014.] Keywords: Reconstruction, Executive and Legislative Authority, Good Governance, Values Welfare.